2019
DOI: 10.3390/molecules24061045
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Inhibit 3T3-L1 Adipogenesis Depending on the Stage of Differentiation and Their Binding Affinity to PPARγ

Abstract: Phenolic compounds might modulate adiposity. Here, we report our observation that polyphenols and phenolic acids inhibit adipogenesis in 3T3-L1 with different intensity depending on the family and the stage of differentiation. While quercetin and resveratrol inhibited lipid accumulation along the whole process of differentiation, apigenin and myricetin were active during the early and latest stages, but not intermediate, contrary to hesperidin. The activity of phenolic acids was limited to the early stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 68 publications
5
50
1
Order By: Relevance
“…The TPC of various extracts in decreasing order was as follows: AE > BE > ME > EE > WE > CE > HE (Figure 1). to bind with particular residues (Phe264, His266, Ile281, Cys285, and Met348) of the PPARγ receptor to establish anti-adipogenicity during the early stages of the differentiation [29]. For example, ethanol extracts of bamboo stems have been shown to play a vital role in the downregulation of differentiation markers C/EBPβ, PPARγ, and FABP4 (fatty acid-binding protein) [30].…”
Section: Phenolic Composition Of Canola Meal Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPC of various extracts in decreasing order was as follows: AE > BE > ME > EE > WE > CE > HE (Figure 1). to bind with particular residues (Phe264, His266, Ile281, Cys285, and Met348) of the PPARγ receptor to establish anti-adipogenicity during the early stages of the differentiation [29]. For example, ethanol extracts of bamboo stems have been shown to play a vital role in the downregulation of differentiation markers C/EBPβ, PPARγ, and FABP4 (fatty acid-binding protein) [30].…”
Section: Phenolic Composition Of Canola Meal Extractsmentioning
confidence: 99%
“…Sinapic acid [27], and hydroxycinnamic acids [28] are known for the lipolysis and their role in anti-adipogenesis. Polyphenols including quercetin, resveratrol, apigenin, and myricetin are known to bind with particular residues (Phe264, His266, Ile281, Cys285, and Met348) of the PPARγ receptor to establish anti-adipogenicity during the early stages of the differentiation [29]. For example, ethanol extracts of bamboo stems have been shown to play a vital role in the downregulation of differentiation markers C/EBPβ, PPARγ, and FABP4 (fatty acid-binding protein) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are molecules that induce apoptosis in different types of cancer by acting specifically on SCD1 [14]. The inhibition of SCD1 through natural compounds can result in health benefits [16][17][18]. The sterculic oil is an extremely precious natural product, capable of inhibiting SCD1 enzyme in obese ob/ob mice, reducing fat accumulation in the liver and adipose tissue and improving inflammation and insulin resistance, factors that create an environment conducive to the development of cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides anti-osteoporotic activities, the phenolic fractions and gallotannins, including penta-O-galloyl-β-D-glucose from NRCs, have been shown to inhibit pancreatic lipase activity involved in fat absorption [11,34]. It has also been shown that phenolic acids (ellagic acid and gallic acid), flavonoids (kaempferol, quercetin, and luteolin), and penta-O-galloyl-β-D-glucose inhibit adipocyte differentiation in 3T3-L1 pre-adipocytes [35][36][37]. In our adipocyte differentiation assay, penta-O-galloyl-β-D-glucose was found to inhibit the adipocyte differentiation of D1 cells at 10 µM (our unpublished data).…”
Section: Resultsmentioning
confidence: 99%